Analisis Kritik Sosial dan Nilai Pendidikan dalam Film “Budi Pekerti” Karya Wregas Bhanuteja Serta Pemanfaatannya Sebagai Bahan Ajar Apresiasi Sastra di SMA - Bunga Aura Cikal; Sopyan Sauri; Henri Henriyan Al Gadri (Jurnal Artikula, 2025)
This study aims to describe the social criticism and educational values contained in the film "Budi Pekerti" by Wregas Bhanuteja, and its use as teaching material for literary appreciation in high school. This study uses a qualitative approach with descriptive methods. The subject of the study was the film "Budi Pekerti" by Wregas Bhanuteja. Data collection techniques were conducted through observation and documentation of dialogue in the film "Budi Pekerti" by Wregas Bhanuteja, which contains social criticism addressing issues of violence, moral issues, educational issues, and technological issues, as well as educational values including honesty, hard work, respect, responsibility, and discipline. Data analysis techniques used the Miles and Huberman content analysis model: data reduction, data presentation, conclusions, and verification. Data were collected through reading, note-taking, and listening, then processed to identify themes and patterns. After conducting the research, the researcher found several findings, namely Social Criticism consisting of 36 data, including 7 data on Violence Problems, 10 data on Moral Problems, 9 data on Education Problems, and 10 data on Technology Problems, while Educational Values amounted to 45 data, including 9 data on Honesty Values, 8 data on Hard Work Values, 12 data on Respect Values, 8 data on Responsibility Values, and 8 data on Discipline Values. Social criticism and Educational Values in Films are very important to be understood, both by the general public and by students in schools. Understanding social criticism helps people become more sensitive to social issues around them, in addition, the educational values conveyed through this film provide good character provisions for students, which are very necessary in everyday life. The research on the Film "Budi Pekerti" by Wregas Bhanuteja can be used as teaching material for literary appreciation in grade XI of high school on Short Story material. This work was chosen because it contains social criticism and educational values relevant for analysis. It has the potential to increase students' interest in literature, foster sensitivity to social issues, and shape character through the appreciation of educational values